Hydroelasto-Plastic Response of a Ship Model in Freak Waves: An Experimental and Numerical Investigation - Liu, Weiqin; Mo, Yining; Xiong, Luonan; Xu, Haodong; Song, Xuemin; Li, Ye (Journal of marine science and engineering, 2024)
Freak waves have caused numerous accidents resulting in the collapse of ship structures due to structural plasticity, buckling, and instability, leading to the loss of life and property. Consequently, there is a growing academic interest in understanding ship structural collapsed responses induced by freak waves. This paper presents both numerical and experimental investigations on the structural collapse response of a ship model caused by freak waves. The study uses the Peregrine breather solution theory based on the Nonlinear Schrödinger (NLS) equation to generate a theoretical freak wave, and the nonlinear time-domain wave elevation and velocity field are obtained. The theoretical history of wave elevation is transferred into the wave maker of the wave tank to create experimental freak waves, and the velocity field of the freak wave is defined in a Computational Fluid Dynamics (CFD) solver to generate 3D numerical freak waves. A similar hydroelasto-plastic model is designed, and a hydroelasto-plastic experiment is conducted to observe experimental freak waves and large rotational deformations. The theoretical velocity field from the Peregrine breather solution theory, based on the NLS equation, is defined in a CFD platform to generate 3D numerical freak waves. A two-way Fluid-Structure Interaction (FSI) numerical hydroelasto-plastic approach coupling of CFD with a nonlinear Finite Element Method (FEM) solver is applied. Co-simulation of wave pressures and the structural collapsed response of the ship model caused by freak waves is performed. The wave elevation of experimental and numerical freak waves and the large rotational deformation of the buckling hinge are analyzed and compared, revealing a good agreement between the experiment and calculation. The maximum simulation rotational angle is 38.9°, while the maximum experimental rotational angle is equal to 42.3° for a typical wave case H2, which means numerical model accuracy and performance are acceptable for the simulating hydroelasto-plastic problem. The findings demonstrate that the numerical approach proposed in this study can effectively solve the hydroelasto-plastic response of ship structures in freak waves, offering a valuable tool for evaluating ship strength in these conditions and guiding future ship structural design.